The leading practice of decision making in modern business systems : innovative technologies and perspectives of optimization - Popkova, Elena G.; Chesnokova, Alina V. (Emerald Publishing Limited, 2019)
Focusing on modern business systems from within the modern Russian context, this book examines how companies can become leading competitors globally within their industries through new decision making processes. Whilst current practices support the sustainability of a business system in terms of maintaining normal functionality and the prevention of crises, there is a need to consider the goals of leading organizations with larger business systems and greater resources. These goals can be more global in their focus and envisage the creation or strengthening of competitive advantages. Contributors of this book explore large scale industries specializing in hi-tech spheres of economy and instigate innovative activity in the face of high-levels of competition. Specific industries analyzed in this content include digital medicine, energy efficiency and car manufacturers. Using models of optimization and a range of real-world case studies, the book provides tools, technological analysis and techniques for practitioners to use within their own decision-making practices. For scholars researching business management, leadership and decision-making, this book also offers a useful insight into how optimized decision-making processes can be applied to the modern business system.